De Falkenau aux ruines de Verboten! (1959), les dialectiques formelles de Samuel Fuller - Vincent Souladié (Transatlantica, 2022)
Before becoming a famous Hollywood director, Samuel Fuller honed his visual sensibility as a soldier whose superior officers had entrusted with the task of filming the liberation of Europe by US troops in 1945. The discovery of the Czechoslovakian town of Falkenau and the nearby concentration camp was a traumatic experience for him, which he evoked forty years later in the documentary Falkenau, The Impossible (1986). The 16 mm footage he recorded there illuminates, in hindsight, the visual style Fuller developed in his films. The confrontation within the same sensible space between the normalized mendacity of the city and the horrors of the concentration camp, which the 16 mm footage explicitly reveals, seems to have had repercussions throughout his feature films, notably though a poetics of heterogeneity and contradiction. This is particularly the case in the opening sequence of his WW2 film Verboten! (1959). Set among the ruins of a German city, it is Fuller’s first film dealing with his memories of the war, the liberation and the discovery of the concentration camps.